Health needs assessment: development of a simplified risk probability scale design for rapid mental health screening in emergency frontline rescue teams - Chen, Yifei; Bo, Yan; Han, Zhuanzhuan; Fan, Guowei (Frontiers in Public Health, 2025)
BackgroundEmergency frontline rescue workers during the COVID-19 pandemic faced elevated psychological risks, yet existing tools lack specificity for crisis contexts.AimTo develop a simplified risk probability scale (SRPS) tailored for rapid self-assessment of depression and anxiety in frontline rescue teams.MethodsThis SRPS study employed a mixed research methodology of questionnaires and systematic reviews. Snowball sampling was applied to collect questionnaire data. Univariate and multivariate analyses were conducted to identify key variables for the SRPS, which was then established using binary logistic regression models and nomograms. Receiver operating characteristic (ROC) curves evaluated the SRPS’s accuracy and sensitivity. A literature review of existing COVID-19 assessment tools in the PubMed database was also carried out.Ethics and disseminationThe study was approved by the Institutional Review Board of the Affiliated Hospital of Yangzhou University (IRB No: YKL08-002). Written informed consent was obtained from all participants.Clinical trial registrationhttps://clinicaltrials.gov/, identifier [ChiCTR2500103976].